Perception of Contemporary History in South Korea : The Formation of Contested Legacy of Syngman Rhee - Huh, Seyeon (My University, 2019)
This thesis explores possible factors in the process of forming one’s history perception. It tries to answer how and why young South Koreans form their history perception on Korean contemporary history by examining a case of Syngman Rhee, the first president of the Republic of Korea. Evaluations on Syngman Rhee in academia are largely divided into two groups: the Rhee advocators and the Rhee opponents. Comparable to this academic confrontation, young generations of South Korea show an evident tendency regarding him. Therefore, this thesis first studied contested evaluations of Rhee’s legacy in an academic level. It also examined about the history textbook crisis started in 2002 with an introduction of authorized Korean contemporary history textbooks. Referring to the argument points of the crisis, a textual analysis of narratives in the six authorized textbooks used during the 7th Educational Curriculum to check their attitudes towards Rhee. Then a survey to find factors affecting one’s history perception was conducted targeting Korean university students who are in their 20s. Based on the result of the survey, it took a closer look at school history education mainly textbooks and teachers, and students’ ability. The thesis pointed out the problem of the history textbook crisis and suggested to pay more attention to students and teachers’ role in learning process rather than textbook narratives.
Keywords: Keywords: Syngman Rhee, Contemporary history, history perception, history war, history education, history textbook, history textbook crisis, South Korea